Residential environmental conditions on housing estates in Yerevan - Sargsyan, Tigran (Hungarian Geographical Bulletin, 2013)
Most housing estates of Yerevan, the capital of Armenia were constructed during communism, mostly between the 1960s and 1980s. The residential environment was shaped according to the typical approaches and styles of the Soviet urban construction: houses of  the same type can be found almost in all 15 capitals of the former USSR. The construction of the so-called “elite” housing stock appeared in different parts of Yerevan in the 2000s. However, due to higher prices, those houses are not widely available. Therefore, housing estates of the communist period still remain the only possible housing for the majority of the population in Yerevan. Nowadays, the residential environment on those housing estates has to face different kinds of problems and challenges: communal, infrastructural, environmental, sanitary, esthetical, etc. In the present paper the author makes an attempt to provide an overview on the residential environment of large housing estates in Yerevan based on survey data and field work.